Prevalence of Latent Tuberculosis Infection among patients with Bronchial Asthma Receiving Inhaled or Oral Corticosteroids - Sajjad Ali, Muhammad Sohrab Khan, Ashfaq ur Rehman (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Latent tuberculosis infection (LTBI) is extremely high in areas where tuberculosis disease is common and it is used as a reservoir to develop a disease. Inhaled or oral corticosteroids are often used to treat bronchial asthma patients, and that type of treatment can weaken cellular immunity and predispose patients to Mycobacterium tuberculosis infection and reactivation, but in the region, there is insufficient evidence of it. Hypotheses: To estimate the LTBI prevalence in patients with bronchial asthma using corticosteroids and comparing LTBI prevalence in patients using inhaled corticosteroids (ICS) versus oral corticosteroids (OCS) users. Methodology: The study was a cross-sectional study carried out at the department of Pulmonology Bacha Khan Medical College, Mardan from January 2023 to June 2023. One hundred adult patients with known bronchial asthma who have been diagnosed with the disease by a physician and have undergone a minimum of four weeks of corticosteroids treatment were enrolled. Participants were divided into ICS and OCS exposed. Symptom screening and chest radiography were used in screening out active tuberculosis. The diagnosis of LTBI was made in the form of tuberculin skin test (positive test 10 mm and above) or interferon-gamma release assay. Demographic factors, the level of asthma, comorbidities, and the pattern of corticosteroids were documented. Chi-square and independent t-tests were used to perform the comparisons with p<0.05 as a statistically significant value. Results: The mean age of participants was 41.6 ± 12.4 years and 58% were female. Sixty patients were receiving ICS only, while 40 had recent or ongoing OCS exposure. LTBI was detected in 28 patients, giving an overall prevalence of 28%. LTBI was significantly more frequent in the OCS group than the ICS-only group (42.5% vs 18.3%, p=0.01). LTBI-positive patients were older than LTBI-negative patients (46.2 ± 11.9 vs 39.7 ± 12.3 years, p=0.02). Diabetes mellitus (35.7% vs 15.3%, p=0.03) and household TB contact (32.1% vs 11.1%, p=0.01) were also significantly associated with LTBI. Conclusion: LTBI was present in almost one-third of the corticosteroid-treated asthma patients. Exposure to oral corticosteroids, older age, and the history of diabetes and previous TB contact were also risk factors, which indicated the importance of targeted LTBI screening in high-burden settings. Keywords: Latent tuberculosis; asthma; corticosteroids; prevalence